Investigation of Tumor Necrosis Factor-Alpha (TNF A) Gene Polymorphism in Patients with Hypertension in Al-Diwaniyah City, Iraq - Ghaidaa Raheem Lateef Al-Awsi (Journal of Global Pharma Technology, 2019)
A study was conducted on 100 in the outpatient whom consulted Al-Diwaniyah Teaching Hospital in Al-Diwaniyah City in the period between October 2017 to April 2018.One hundred blood samples (50 experimental and 50 controls) were collected under the supervision of the treating physician. TNF-α, which is an abbreviation of “tumor necrosis factor alpha”, is one of the key distinctive pro-inflammatory cytokines emerging evidence have confirmed the vital role of TNF-α in the progress of hypertension. The genotyping regarding (TNF a) were carried out through utilizing polymerase chain reaction, commonly denoted as (PCR), along with (RFLP), which is an abbreviation of “restriction fragment length polymorphism”. We aimed at determined vital variations within the genotype frequencies of (TNF a) among control and experimental sample groups.Keywords: Hypertension, RFLP, TNF A, SNPs. Polymorphisms, Diwaniyah, Iraq